Inquisition and Knowledge, 1200-1700 - Biller, Peter; Sackville, L. J.; Bird, Jessalynn; Sala, Alessandro; Feuchter, Jörg; Kras, Paweł; Bueno, Irene; Välimäki, Reima; Poznański, Adam; Kieckhefer, Richard (Heresy and Inquisition in the Middle Ages Ser., 2022)
Essays considering how information could be used and abused in the service of heresy and inquisition.